2005
DOI: 10.1093/carcin/bgi194
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide sensitizes ultraviolet (UV)-B-induced apoptosis via protein kinase C-dependent pathways

Abstract: Parthenolide (PN) is the principal sesquiterpene lactone in feverfew (Tanacetum parthenium) with proven anti-inflammatory properties. We have previously reported that PN possesses strong anticancer activity in ultraviolet B (UVB)-induced skin cancer in SKH-1 hairless mice. In order to further understand the mechanism(s) involved in the anticancer activity of PN, we investigated the role of protein kinase C (PKC) in the sensitization activity of PN on UVB-induced apoptosis. Several subtypes of PKC have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…UVB causes apoptosis in JB6 cells through complex mechanisms; it may be mediated by oxidative stress, PKC, or a p53-dependent manner (12,43,44). The signaling pathways for UVB-mediated autophagy and apoptosis may or may not overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVB causes apoptosis in JB6 cells through complex mechanisms; it may be mediated by oxidative stress, PKC, or a p53-dependent manner (12,43,44). The signaling pathways for UVB-mediated autophagy and apoptosis may or may not overlap.…”
Section: Discussionmentioning
confidence: 99%
“…JB6 cells have been extensively used to study the mechanisms of epidermal cell transformation (911). UVB causes the death of JB6 cells in the form of apoptosis (12). We demonstrated that UVB activated autophagy in JB6 cells, and autophagy appeared to be a protective response to UVB-induced damage.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the pan-PKC inhibitor GF109203X suppressed ERK and p38 activation and apoptosis induced by 4HPR, suggesting that PKC may be an upstream regulator of ERK in our system. Others have reported that PKCdelta is upstream of changes in mitochondrial memebrane leading to cytochrome c release (Liao et al, 2005) and PKCzeta is upstream of p38 MAPK activation in UVB-induced apoptosis (Won et al, 2005). ROS may be upstream of PKC because it has been shown that PKC-dependent induction of p21WAF1 by phorbol ester was inhibited by antioxidant (Traore et al, 2005).…”
Section: Hpr-induced Apoptosis In Hnscc Cellsmentioning
confidence: 99%
“…This indicates that high glucose suppresses expression of ENT1 in CFs by activating PKC‐ζ and both ERK1/2 and p38 MAPK signaling pathways. It has been already demonstrated that PKC‐ζ has the ability to activate both the Raf‐1/MEK/ERK1/2 cascade (Berra et al, 1995) and p38 MAPK (Buteau et al, 2001; Won et al, 2005). However, simultaneous activation of ERK1/2 and p38 MAPK pathways in the same cell is relatively rare occurrence.…”
Section: Discussionmentioning
confidence: 99%